THE SPECIFICS OF PRESCRIBING TRIPLE ANTITROMBOTIC THERAPY WITH RIVAROXABAN IN PATIENTS WITH ATRIAL FIBRILLATION AFTER CORONARY ARTERY STENTING - N. A. Novikova; A. S. Shilova (Атеротромбоз, 2017)
A trial fibrillation occurs in 5 to 8% of patients who underwent percutaneous coronary intervention (PCI) with stenting. It is known that dual antiplatelet therapy (a combination of P2Y12 receptor inhibitor and acetylsalicylic acid) significantly reduces the risk of developing stent thrombosis in comparison with vitamin K antagonists; however, anticoagulants are significantly more effective in reducing the risk of ischemic stroke in patients with atrial fibrillation (AF). When opting for a long-term triple antithrombotic therapy, the risk of hemorrhagic complications increases dramatically, while choosing less intensive treatment results in an increased risk of ischemic complications, primarily, ischemic stroke and stent thrombosis. The current recommendations come down to the prescription of all of the three components of antithrombotic therapy. However, this approach leads to a significant increase in the frequency of hemorrhagic complications. The purpose of recent randomized trials was to compare and evaluate the efficacy and safety of different regimens with antithrombotic drugs in combination with rivaroxaban in patients with AF who underwent PCI.